ASSESSMENT OF CULTURAL ENTREPRENEURSHIP MANAGEMENT IN LATVIA - Ieva Zemīte (Mokslo Taikomieji Tyrimai Lietuvos Kolegijose)
A cultural entrepreneur in the twenty-first century will redefine entrepreneurship. A business entrepreneur typically measures performance in profit and return, whereas a cultural entrepreneur assesses success in terms of the impact it has on society as well as in profit and return. Cultural enterprises are for ‘more-than-profit,’ using blended value business models that combine a revenue-generating business with a social-value-generating structure or component. Therefore it is important to measure management of cultural entrepreneurship in order to improve efficiency and stability of cultural entrepreneurship. The purpose of this paper is to define the tools of the measurement of cultural entrepreneurship management, and to investigate the understanding of the stakeholder engagement in cultural enterprises in Latvia. During the research the qualitative research methodology has been used, being oriented towards the research problems which are comprehensible by intervention based in experience and ability to reach broad perspective and evaluate the impact of culture. The research was started by creating a focus group with managers working in the field of Latvian cultural entrepreneurship with experience of at least 5 years. The evaluation of the cultural enterprises’ stakeholders by the method of interview was performed in 42 cultural enterprises: art galleries, non-governmental theatres and concert organizations, thus covering all the legal entities working in the above-mentioned field in Latvia during the research period (2010 – 2013). This is the first study that measures the stakeholder engagement in cultural entrepreneurship and gives a model for assessment of cultural entrepreneurship management.